Landasan Sosiologi Pendidikan Kristen dan Pengaruhnya pada Pendidikan Kristen Modern - Martha Bela Wawo (PT. Penerbit Tiga Mutiara, 2024)
Christian education not only provides religious knowledge but also builds character and unites communities. Therefore, education must be built with a deep conceptual sistematics to understand the complex relationship between religion, society, and education which will be based on the foundation of the sociology of Christian education one of which is by understanding the sociology of education. The sociological foundation of education is very important because it can maintain the values of the Christian faith in education while overcoming global challenges and technological advances in the midst of today's modern world. The sociology of Christian education is a solid and strong foundation to respond to changing times without losing the values or core identity of the Christian faith. The sociology of Christian education will maintain how the values and principles of the truth of the Christian faith are related to the way believers live their lives. It is intended to assist each believer in carrying out his or her calling in the world and help reach souls for Christ. Therefore, it is expected that Christian education must continue to adapt to the changing times by maintaining the principles and values of Christian teaching. This study aims to contribute to Christian Education teachers in facing various challenges as a result of rapid technological development. Sociology of Education plays an important role in modern Christian education in order to understand social dynamics, build character, and build a strong community. by maintaining Christian values that pattern and give meaning to each stage of education, without reducing moral values. Therefore, it is expected for Christian education to adapt to the changing times while maintaining the principles and values of Christian teachings.